Development of polycationic amphiphilic cyclodextrin nanoparticles for anticancer drug delivery - Varan, Gamze; Benito, Juan M.; Mellet, Carmen Ortiz; Bilensoy, Erem (Beilstein Journal of Nanotechnology, 2017)
Background: Paclitaxel is a potent anticancer drug that is effective against a wide spectrum of cancers. To overcome its bioavailability problems arising from very poor aqueous solubility and tendency to recrystallize upon dilution, paclitaxel is commercially formulated with co-solvents such as Cremophor EL® that are known to cause serious side effects during chemotherapy. Amphiphilic cyclodextrins are favored oligosaccharides as drug delivery systems for anticancer drugs, having the ability to spontaneously form nanoparticles without surfactant or co-solvents. In the past few years, polycationic, amphiphilic cyclodextrins were introduced as effective agents for gene delivery in the form of nanoplexes. In this study, the potential of polycationic, amphiphilic cyclodextrin nanoparticles were evaluated in comparison to non-ionic amphiphilic cyclodextrins and core–shell type cyclodextrin nanoparticles for paclitaxel delivery to breast tumors. Pre-formulation studies were used as a basis for selecting the suitable organic solvent and surfactant concentration for the novel polycationic cyclodextrin nanoparticles. The nanoparticles were then extensively characterized with particle size distribution, polydispersity index, zeta potential, drug loading capacity, in vitro release profiles and cytotoxicity studies.Results: Paclitaxel-loaded cyclodextrin nanoparticles were obtained in the diameter range of 80−125 nm (depending on the nature of the cyclodextrin derivative) where the smallest diameter nanoparticles were obtained with polycationic (PC) βCDC6. A strong positive charge also helped to increase the loading capacity of the nanoparticles with paclitaxel up to 60%. Interestingly, cyclodextrin nanoparticles were able to stabilize paclitaxel in aqueous solution for 30 days. All blank cyclodextrin nanoparticles were demonstrated to be non-cytotoxic against L929 mouse fibroblast cell line. In addition, paclitaxel-loaded nanoparticles have a significant anticancer effect against MCF-7 human breast cancer cell line as compared with a paclitaxel solution in DMSO.Conclusion: According to the results of this study, both amphiphilic cyclodextrin derivatives provide suitable nanometer-sized drug delivery systems for safe and efficient intravenous paclitaxel delivery for chemotherapy. In the light of these studies, it can be said that amphiphilic cyclodextrin nanoparticles of different surface charge can be considered as a promising alternative for self-assembled nanometer-sized drug carrier systems for safe and efficient chemotherapy.
Keywords: amphiphilic cyclodextrin; anticancer; nanoparticle; paclitaxel; polycationic